Changes of Peripheral Blood Lymphocyte Subtypes in Patients with End Stage Cancer Administered Localized Radiotherapy and Bojungikki-Tang. (20th February 2014) - Lee, A-Jin; Lee, Ho Jun; Kim, Jong-Dae; Jung, Hyun-Jung; Bae, Sung Hwa; Ryoo, Hun Mo; Kim, Sang-Gyung
Abstract : Localized radiotherapy (RT) can cause immune dysfunction. Bojungikki-tang is known to restore immune function. We investigated the absolute counts and percentages of peripheral blood (PB) lymphocyte subtypes in end stage cancer patients before and after RT and after oral administration of Bojungikki-tang water extract (BJITE) and to evaluate the changes mediated by RT and BJITE. Absolute counts and percentages of lymphocyte and lymphocyte subsets were determined in whole blood using the TetraONE System (Beckman Coulter, USA). Flow cytometry results were compared before and after RT and after administration of BJITE. Absolute numbers of CD3+, CD4+, and CD8+ T cells and CD19+ B cells decreased significantly after RT (P < 0.05 ). Absolute numbers of CD3-CD56+ cells did not change in both groups. No significant differences were observed in the absolute counts of lymphocyte subtypes before and after administration of BJITE or vitamin group. When BJITE group was compared with vitamin group, absolute numbers of CD19+ B cells increased. RT-induced decrease in T cells and B cells in PB suggests that immune deterioration occurs after RT. Administration of BJITE might be effective in the restoration of number of B cells.